RELASI PEKERJA PEREMPUAN (Studi Kasus Pada Usaha Pengolahan Kopra Di Parit No.02 Mulya Desa Kayu Raja Kecamatan Keritang Kebupaten Indragiri Hilir) - Desti "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in Kayu Raja Village, Keritang District, Indragiri Hilir Regency with the aim of knowing the activities of women workers in the copra processing business and describing the working relationship between toke (copra processing business owners) and women workers in copra processing businesses. This study uses descriptive qualitative research methods. Data collection was carried out using in-depth interview techniques, direct observation and documentation. The results of the analysis show that there are several work activities carried out in the copra processing business, starting from the process of opening the crest, cleavage, transportation, drying, collecting coconuts, gouging, the process of dividing the shell and the process of burning the shell which will become charcoal. Copra processing workers come from the Bugis tribe so that in interacting they use symbols, namely the Bugis language. The results of the analysis of research observations show that there is a strong relationship between female workers and toke, supported by kinship ties and ethnic similarities which are the capital for forming relationships. There is a social exchange that creates a reciprocal relationship between toke and workers so that the relationship is maintained, where if workers have problems they will ask for help to toke both materially and non-materially. Although wages are in the form of shells, there is a greater value obtained than wages, namely the assistance provided.  Keywords: Relationship, Female Workers, Coconut Copra